2020
DOI: 10.1038/s41467-020-16584-z
|View full text |Cite
|
Sign up to set email alerts
|

Core functional nodes and sex-specific pathways in human ischaemic and dilated cardiomyopathy

Abstract: Poor access to human left ventricular myocardium is a significant limitation in the study of heart failure (HF). Here, we utilise a carefully procured large human heart biobank of cryopreserved left ventricular myocardium to obtain direct molecular insights into ischaemic cardiomyopathy (ICM) and dilated cardiomyopathy (DCM), the most common causes of HF worldwide. We perform unbiased, deep proteomic and metabolomic analyses of 51 left ventricular (LV) samples from 44 cryopreserved human ICM and DCM hearts, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 78 publications
8
54
0
Order By: Relevance
“…Although we did not observe significant differences in these key echocardiographic, histopathologic, and molecular markers of cardiac dysfunction, there may be sex-related differences in the molecular pathways leading to such outcome. This notion is supported by a recent study revealing sex-specific differences in cardiac proteomic and metabolomic profiles between men and women with a similar degree of human heart failure [46] and thus warrants further investigation.…”
Section: Plos Onesupporting
confidence: 58%
“…Although we did not observe significant differences in these key echocardiographic, histopathologic, and molecular markers of cardiac dysfunction, there may be sex-related differences in the molecular pathways leading to such outcome. This notion is supported by a recent study revealing sex-specific differences in cardiac proteomic and metabolomic profiles between men and women with a similar degree of human heart failure [46] and thus warrants further investigation.…”
Section: Plos Onesupporting
confidence: 58%
“…Similarly, these DEGs were also markedly involved in in ammatory/immune response, response to stress, oxidative stress, and brosis. The exact same terms enriched from DEPs and DEGs furtherly highlighted the key roles of the processes of ECM organization and response to stress, as well as the complement and coagulation cascades signal pathway, in the mechanisms of ICM, which were consistent with previous researches [19][20][21].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the DIA approach was used to identify the abundances as well as the changes of proteins in ICM, and a total of 546 proteins (including 377 up-and 169 down-regulated DEPs) were differentially expressed compared with NFD. Previous studies have revealed multiple cellular pathophysiologies involved in ICM, such as oxidative stress, in ammation, mitochondrial dysfunction, apoptosis cascade, calcium overload, myocardial brosis, and so on [4,18,19]. Similarly, our results of the GO and pathway analysis also suggested that these DEPs participated in cardiac muscle structure development/organization and contraction, oxidative stress, energy metabolism, lipid metabolism, responses to stress and nucleotide metabolism, ECM organization, and immune responses.…”
Section: Discussionsupporting
confidence: 76%
“…Recent studies have suggested gender-specific perturbations of some metabolites like microbiome-derived metabolite trimethylamine N-oxide (TMAO) in heart tissues. TMAO was elevated in male ICM and DCM compared to male donor hearts, whereas it was not significantly different between female HF and female donor hearts ( 18 ). These findings permitted a better understanding of divergent HF pathogenesis between males and females.…”
Section: Discussionmentioning
confidence: 96%
“…R2Y (cum), Q2 (cum), and permutation test were used to evaluate the stability and predictability of the model. Differential metabolites by disease groups (DCM vs. healthy controls and ICM vs. healthy controls) adjusted for age, gender, and medication use were determined by linear modeling using the lmFit and eBayes functions implemented in the limma R package (17,18). The P-values were adjusted by Benjamini-Hochberg method to account for multiple testing.…”
Section: Discussionmentioning
confidence: 99%